BREASTFEEDING PRACTICES AND HISTORY OF INFECTIOUS DISEASES AS DETERMINANTS OF STUNTING AMONG CHILDREN AGED 12–59 MONTHS IN PESAWARAN REGENCY - Widyantari, Kadek Yuke; Hidayati, Rizka Dita; Fatriani, Rully (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Stunting remains a public health problem in Indonesia, especially in rural areas. Breastfeeding practices and infectious diseases play an important role in child growth. This study aims to analyse the relationship between breastfeeding practices and infectious disease history with stunting in children aged 12–59 months in Pesawaran District. This study used a case-control design with 210 respondents (105 stunted, 105 not stunted) selected through purposive sampling. Data were collected through interviews and anthropometric measurements according to WHO standards. Analysis was performed using chi-square tests and multiple logistic regression. There was a significant relationship between breastfeeding practices and history of infectious diseases with the incidence of stunting (p0.05). Children who did not receive exclusive breastfeeding had a two times higher risk of stunting (AOR=2.10; 95% CI: 1.13–3.88). Children without a history of acute respiratory infections had a lower risk of stunting (AOR=0.48; 95% CI: 0.26–0.88). Exclusive breastfeeding and prevention of infectious diseases are important factors in preventing stunting. Efforts to educate on breastfeeding, improve clean and healthy living behaviours, and prevent infections need to be strengthened at the family and community levels.